BUILDING PESANTREN ENTREPRENEURSHIP THROUGH INTERNAL INITIATIVE AND EXTERNAL DEVELOPMENT - Muhardi Muhardi; Dedih Surana; Nandang Ihwanuddin; Handri Handri (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The objective of this research is to analyze the role of internal initiative driven by pesantren leaders and external development provided by the government in building pesantren entrepreneurship. This research was conducted by utilizing a descriptive qualitative method, with a sample of 5 pesantrens in Garut Regency, Indonesia. The data obtained in this research was collected through focus group discussion (FGD) with a number of stakeholdrs as informant namely leaders of the 5 pesantrens taken as sample along with a couple of their students. Based on field study, we discovered that the success of pesantren in building entrepreneurship activities are dominantly determined by internal initiative and creativity driven by entrepreneurs/managers/ initiators of pesantren, supported by their students. Other pesantrens that have succeeded to build their economic independencies have also received assistance from the government through one pesantren one product (OPOP) program as external development driving factor, which motivated these pesantrens to contribute and to help the government to achieve the goals of this program.